DEVELOPMENT OF THE MINAPOLITAN VILLAGE CSR PROGRAM MODEL PT. PERTAMINA RU II DUMAI - Wedayanti, Made Devi; Yogia, Moris Adidi; Prihatin, Panca Setyo; Pulungan, Boby Indra; Desriadi, Desriadi (Natapraja, 2023)
In an effort to improve the welfare of the fishermen community, PT. Pertamina RU II Dumai created the Minapolitan Village CSR program. However, in the implementation of the program there are still problems, First, the Minapolitan village development program has not made the right contribution to the results desired by the TUNA fishermen group. The second problem is that the form of assistance provided for the Minapolitan Village Program often fails and does not generate any profit for the Tuna Fishermen's Group. The aim of the research is to analyze the Development of the Minapolitan Village CSR Program Model PT. Pertamina RU II Dumai to the Tuna Fishermen Group. The research method uses qualitative methods. The findings on the Leadership indicator are implemented, the Proportion of Assistance indicator is quite implemented, the Transparency and Accountability indicator is Enough Implemented, the Area Coverage indicator is implemented, the Planning indicator is implemented, the Stakeholder Engagement indicator is Enough Implemented, the Sustainability indicator is not implemented enough, and the Real Results indicator is quite feasible. The conclusion of this study is the development of the Minapolitan Village CSR Program model by PT. Pertamina RU II Dumai for the Tuna Fishermen Group is more maximized on indicators that are quite implemented and not implemented.